Morphometric comparison of human died spermatozoa and pets, dyed with the color of christmas tree (2016)
At the forensic analysis level regarding the collected samples on sex crimes when semen is the body fluid which is evidence in a criminal act since one of its components are sperm and these cells are specific and retained for a longer perior of time because they contain DNA and 200 to 400 million sperms are found in a normal ejaculate (1); for this reason, these cells are an important tool in the administration of justice. Although researchers found no relationship between sex-related crimes and animals, it is very important to build a difference between the morphological characteristics between human sperm and animal sperm daily connected to the man.The goal of this document is to determine the differences between human and animal sperm by using the christmas tree coloring method as well as the microscopic observation. A human semen sample was collected from some domestic animals ejaculation like bull, hamster, horse, dog, pig and cat by an extended process which was developed, stained and analyzed under the light microscope, finding some significant differences in the studied species sperm and in which the shape, size and color were outstanding allowing to identify the characteristics of each species. The most similar characteristics were found between the man´s sperm and the dog´s sperm. The difference between man´s sperm and the animal´s one is very important at the time of solving forensic cases. The morphometric study revealed some clear differences between the analyzed sperm which will be a very important tool when seeking a given sample.